The Effectiveness of Environmental Legal Instruments in Addressing the Dynamics of International Trade - Syahrul Ramadhan Sihotang; Jalaluddin Ritonga; Niat Marisi Nainggolan; Noval Syahputra Hasibuan; Baginda Baginda; Khomaini Khomaini (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2025)
The era of economic globalization requires Indonesia to adapt its environmental legal instruments to the increasingly complex dynamics of international trade. The regulatory transformation through Law No. 6 of 2023 on Job Creation has shifted the paradigm from an “environmental permit” system to an “environmental approval” system, while the implementation of carbon taxes through Law No. 7 of 2021 and various related conservation regulations presents new challenges in balancing economic competitiveness and environmental protection. This study aims to analyze the effectiveness of Indonesia's environmental legal instruments in meeting international environmental standards such as the EUDR and CBAM. The research method employs a normative legal approach using library research techniques, examining primary legal sources such as the latest laws and their implementing regulations, as well as secondary sources from academic literature and international reports. The results of the study show that environmental regulatory transformation creates a paradox between deregulation to attract investment and increasing environmental standards demanded by the global market. The implementation of a carbon tax at a rate of Rp30,000 per ton of CO2e and a carbon trading mechanism shows progressive steps but is still limited in scope. The development of synergies between conservation and trade requires strengthening the Payment for Environmental Services scheme and sustainable product certification. The study's conclusions emphasize the need for a more balanced policy reorientation and a holistic approach to integrate economic, social, and environmental aspects in addressing the dynamics of international trade that prioritize sustainability principles.